If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2 + 3x) = 3(3 + x) + 4 (2 * 2 + 3x * 2) = 3(3 + x) + 4 (4 + 6x) = 3(3 + x) + 4 4 + 6x = (3 * 3 + x * 3) + 4 4 + 6x = (9 + 3x) + 4 Reorder the terms: 4 + 6x = 9 + 4 + 3x Combine like terms: 9 + 4 = 13 4 + 6x = 13 + 3x Solving 4 + 6x = 13 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + 6x + -3x = 13 + 3x + -3x Combine like terms: 6x + -3x = 3x 4 + 3x = 13 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + 3x = 13 + 0 4 + 3x = 13 Add '-4' to each side of the equation. 4 + -4 + 3x = 13 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 13 + -4 3x = 13 + -4 Combine like terms: 13 + -4 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 10-2lnx=3 | | x+2(9-8x)=3 | | 2b=-5 | | 14-(6-3x)=4x-x | | 8+6a=-2q+24 | | 5ln(X-4)=7 | | -3n+1=-113 | | x^2-7x-36=0 | | 3y+5=3x+5 | | 2x^2+14x+24= | | 4(3-3x)-8x=15-2(5x-8) | | 16x=13x+45 | | 4r^2-49= | | 17+n-2-6=n+9 | | 5+10-3=4x | | (3x+50)=(7x-10) | | 2y+4=x-10 | | 6b-12=10+8b-4b | | 3(2y-5)= | | 2(x^3-3x^2-3x+9)=0 | | 5y^2-4x^2=20 | | 30a^2b^3c^4-20a^5b^2c^3+10a^3bc^2= | | (6y-16)=(4y+6) | | a+b=4 | | 3r-2+5r=2r+12 | | 10x+3y-9=0 | | (Y-4)(y-7)= | | 6x-13=2x-5 | | 3x-18=x+10 | | w^2+16=8w | | 2x+5x=3.5 | | 10y+2=x-6 |